2015
DOI: 10.1037/a0038549
|View full text |Cite
|
Sign up to set email alerts
|

Diversity statements: How faculty applicants address diversity.

Abstract: The purpose of the present study was to examine application materials for assistant professor positions in 3 academic disciplines. Applicants were asked to write a diversity statement describing how they would advance diversity through their research, teaching, and service. The sample included application materials submitted by 191 candidates for tenure-track faculty positions at a public research university in computer science, political science, and psychology. Application letters and diversity statements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
0
13
0
1
Order By: Relevance
“…Instead, if identity characteristics were mentioned, they were tied to the impact of that identity on their approaches, actions, or interests in relation to the faculty role they were seeking. Furthermore, prior research by Baker, Schmaling andcolleagues (2015, 2016) found very low rates of applicants' identity self-disclosures in their diversity statements, especially for underrepresented or minoritized identities. Our case example did not show this pattern.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead, if identity characteristics were mentioned, they were tied to the impact of that identity on their approaches, actions, or interests in relation to the faculty role they were seeking. Furthermore, prior research by Baker, Schmaling andcolleagues (2015, 2016) found very low rates of applicants' identity self-disclosures in their diversity statements, especially for underrepresented or minoritized identities. Our case example did not show this pattern.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the increasing attention paid to diversity statements, little systematic research has investigated these statements and their content, that is, the types of views, experiences, and skills that are described in these statements. To our knowledge, the only research on faculty diversity statements are two studies by Baker, Schmaling and colleagues that focused largely on coding applicants' conceptualization of diversity (e.g., identity categories such as age, ethnicity/ race, gender, sexual orientation) and how applicants disclosed and described their own diversity characteristics (Baker, Schmaling, Fountain, Blume, & Boose, 2016;Schmaling, Trevino, Lind, Blume, & Baker, 2015). These studies provide important insights into the varying identity-based terms that applicants use to reflect their diversity contributions, as well as the overall low disclosure in selfidentification among underrepresented or minoritized groups.…”
Section: Introductionmentioning
confidence: 99%
“…Given the influence of a salient social identity on a group's functioning, the question regarding the existence of social identity among the culturally diverse HE faculty in Oman pertains. While the literature suggests that the academic discipline could form the basis for group identity in academia (Blackwell et al, 2009;Clarke et al, 2013;Schmaling et al, 2014), the mix of cultural identities characterizing Omani HE is likely to hinder the salience of a unified academic/professional identity. This is especially so that academic faculty members are mostly non-Omanis, which means that longevity within the group could be affected by the constant movement of members from and to the group.…”
Section: Group Identity and The Vision Of Omani Higher Educationmentioning
confidence: 99%
“…If libraries were to require candidates to demonstrate their experience working in a diverse and inclusive environment or demonstrate their commitment to DEI in the workplace this would send a strong and positive signal to prospective applicants. A practical approach may be for applicants to include a diversity and inclusion statement as to how they will advance diversity and inclusion in their work as part of the application package; this is an emerging practice in faculty searches (Schmaling et al, 2015).…”
Section: Limitationsmentioning
confidence: 99%